Leverage change, debt overhang, and stock prices - CAI, Jie (Institutional Knowledge at Singapore Management University, 2011)
We document a significant and negative effect of the change in a firm's leverage ratio on its stock prices. We find that the negative effect is stronger for firms that have higher leverage ratios, higher likelihood of default, and face more severe financial constraints. Moreover, firms with an increase in leverage ratio tend to have less future investment. These findings are consistent with Myers' (1977) debt overhang theory that an increase in leverage may lead to future underinvestment, thus reducing a firm's value.